Navigating Bank Decline: Are Mergers the Key to Recovery? - Anders Kjellman; Risto Tainio; Taisto Kangas (Business, Management and Economics: Research Progress Vol. 9, 2024)
Aim: The aim of the study is to present a model of bank management during a decline in which mergers are used as a way forward. Thereby, bank mergers are being investigated as a recovery recipe. Study Data and Design: Bank mergers and acquisitions (M&A) have been analyzed in Finland from 1990-2024. In the previous study of 309 Finnish bank mergers from 1990-2013 [1], it was found that many bank managers gradually lost their confidence concerning their capability of successfully running their banks, thus choosing to merge. Hence, research was done to investigate if new M&A data from 2014-2024 would confirm the previous study. Results: Based on 309 Finnish bank mergers from 1990 to 2013 and 41 bank mergers from 2014 to 2024, it was found and confirmed that many bank managers gradually lost their confidence concerning their capability of successfully running their banks, thus choosing to merge. The explicit factor behind bank decline usually relates to an economic downturn and bad banking. New M&A factors in the 21st century are increasing banking regulation and technical development. Somewhat surprisingly, it was found that the decline in banking cannot be understood without looking at growth before the decline. However, the implicit, triggering factor behind bank decline relates to bank management. The available options for crisis bank management besides mergers are to cut costs, increase income, get more own capital, manipulate bookkeeping data, sell the bank, buy banks or declare failure. Given these options bankers and board members choose to merge. Conclusion: Banks that are not involved in mergers or acquisitions perform better. It is the less viable banks that enter into an M&A process after a crisis period. Mergers in general cause value destruction. However, they may be the only perceived way of continuation of banking activity. Therefore, mergers play a vital role!